2022
DOI: 10.1021/acs.inorgchem.2c03546
|View full text |Cite
|
Sign up to set email alerts
|

Two Stable Cd-MOFs as Dual-Functional Materials with Luminescent Sensing of Antibiotics and Proton Conduction

Abstract: Construction and investigation of dual-functional metal−organic frameworks (MOFs) with luminescent sensing and proton conduction provide widespread applications in clean energy and environmental monitoring fields. By selecting a phosphonic acid ligand 4-pyridyl-CH 2 N(CH 2 PO 3 H 2 ) 2 (H 4 L) and coligand 2,2′-biimidazole (H 2 biim), two cadmium-based MOFs [Cd 1.5 (HL)-(H 2 biim) 0.5 ] (1) and (H 4 biim) 0.5 •[Cd 2 (L)(H 2 biim)Cl] (2) with different structures and properties have been hydrothermally synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 91 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have indicated that luminescent quenching effects are mainly caused by electron and energy transfer, as well as structure collapse [50,51]. As the first and foremost evaluation indicator, the stability of frameworks plays a crucial role and directly determines the actual values and application scenarios [52][53][54][55]. Fortunately, the structure collapse of ZnHoMOF can be excluded by comparing the PXRD profiles of reused crystalline materials with the original ones (Figure S9).…”
Section: Possible Mechanism For Luminescence Sensingmentioning
confidence: 99%
“…Prior studies have indicated that luminescent quenching effects are mainly caused by electron and energy transfer, as well as structure collapse [50,51]. As the first and foremost evaluation indicator, the stability of frameworks plays a crucial role and directly determines the actual values and application scenarios [52][53][54][55]. Fortunately, the structure collapse of ZnHoMOF can be excluded by comparing the PXRD profiles of reused crystalline materials with the original ones (Figure S9).…”
Section: Possible Mechanism For Luminescence Sensingmentioning
confidence: 99%
“…The first approach is to reduce the activation energy of proton transfer or/and increase the number of proton carriers (such as H 2 O, NH 4 + , H 3 O + ). , However, it still confronts challenges in the current situation due to the fact that this method needs to comprehensively consider various factors that may affect the performance of proton conduction. The other approach is to introduce more acidic functional groups such as carboxylic acids, , sulfonic acids, , or phosphonic acids to enhance their acidity and hydrophilicity, thereby enriching the presence of hydrogen-bonding networks. Evidently, the second method is more meaningful for improving proton conductivity owing to its chemical stability and structural diversity accompanied by the simple and facile operation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…8,[13][14][15][16][17][18] Similar to frequently-used photoactive groups such as azobenzenes, porphyrins, triphenylamines, and pyrenes, lophine possesses excellent photophysical and chemical properties and is capable of generating specific sensing properties in response to different external stimuli. [19][20][21][22][23] However, unlike the synthesis process of ligands containing the above conjugated units, the design and synthesis of lophine derivatives are relatively simple. For example, a variety of dilophine ligands with D-A-D configuration, which can effectively enhance the shortrange transfer efficiency of photogenerated electrons by modulating the energy level structure of the central acceptor, have been developed.…”
Section: Introductionmentioning
confidence: 99%